Parenting for Lifelong Health program for parents and teens in Zimbabwe: cost estimation and the budget impact analysis - Zwidza, Yolanda Rutendo (Unknown, 2025)
Introduction Parenting for Lifelong Health (PLH) for adolescents was initiated in 2012 to address the pervasive issue of childhood violence in low-to-middle-income countries. The intervention targets teens aged 10-17 years old and their caregivers. The program outcomes aim to increase positive parenting, reduce harsh discipline, and the reduction of behavioural problems in teenagers. Secondary outcomes include increasing the parents' self-efficacy. Methods This thesis evaluates the total and unit costs of the Parenting for Lifelong Health for Teens (PLH-Teens) program in Zimbabwe and estimates the budgetary impact of scaling up the intervention nationally. An economic cost analysis was conducted from the provider's perspective to calculate the total cost of implementing the program over one financial year, using the 2021 USD rate. The total cost of delivering the intervention to 5537 families was determined by summing capital and recurrent costs, with capital costs annuitized at a 5% discount rate. A budget impact analysis was then performed to estimate the financial implications of scaling the program to 250,000 families. Additionally, a one-way sensitivity analysis was carried out to examine potential variations in cost outcomes by making assumptions and changes to the input variables. Results The total implementation cost of the PLH-Teens program for 5537 participants in the year 2021 was US $823,704.00 The unit cost per family (completing sixteen sessions) was US $148.76, and the unit cost per session was US $9.30. Scaling the program to 250,000 families, representing an approximate increase of 96.36% of the initial target population, resulted in an estimated budget impact of US $37 190 915.00. The budget impact analysis indicated that the total cost of implementing the PLH program exceeded the national government budget allocation for programs that address violence in orphaned and vulnerable children and teens of US $27 000 000.00. Conclusion Parenting programs indicated high efficacy in the reduction of violence between caregivers and teenagers in Zimbabwe, following extensive modification of the intervention design to accommodate the context of low- to middle-income countries in their various dimensions. The socioeconomic profile of Zimbabwe has limitations in the ability to implement the intervention without donor assistance independently.